A literature review of the pollination strategies and breeding systems in Oncidiinae orchids - Jonas B. Castro; Rodrigo B. Singer (Acta Botânica Brasílica, 2019)
ABSTRACT Oncidiinae is an exclusively Neotropical orchid subtribe with about 1600 described species and an impressive array of vegetative and floral morphological adaptations. We present the results of a literature survey on the pollination strategies and breeding systems of this orchid subtribe. The flowers are pollinated by a wide range of insects (mostly bees) and, sometimes, hummingbirds. Several genera reward their pollinators with floral resources such as oils, nectar or perfumes. Whereas pollination by oil-gathering bees likely evolved several times within Oncidiinae, exclusive pollination by perfume-gathering male Euglossine bees is likely restricted to a set of closely-related genera. Pollination by food or sexual deception is also present within the subtribe. Up to date, the pollen-vectors of the 92 species of Oncidiinae studied so far are as follows: 84.7 % are pollinated by bees, 6.5 % by wasps, 4.3 % by hummingbirds, 3.2 % by butterflies and 3.2 % by flies. Oncidiinae orchids are preferentially self-incompatible (69.4 % of the species studied so far), some may also present protandry as a mechanism to promote cross-pollination. Fruiting success is generally low. The rate of visitation with subsequent pollination is low, in general, which contributes to the low reproductive success of this plant group.